A green revolution in Mozambique: a study about the government possibilities to launch a sustainable green revolution - Rodrigues, André Luiz da Anunciação (2009)
The present study is focused on the analysis of the political, economical and social factors that may interfere with the possibility of a Green Revolution as a solution for Mozambique to reach self-sufficiency and to reduce poverty. In order to perform such analysis, the study analyzes the consequences of the decolonization process in Mozambique focusing that the independence process in Mozambique did not create non-colonial models for the Agriculture Sector. Later on, the study tries to understand the impact of HIV/AIDS and Malaria on the labor force. By then, it explores the concepts of the Green Revolution and its successful history in India. At the end, it tries to evaluate if a Green Revolution is possible in Africa, especially in Mozambique, first identifying the factors, which characterized the Green Revolution in India, and trying to link those factors with the reality of Mozambique. The report is structured as followed; Chapter 2, ¿The decolonization process and its impacts on the agriculture sector¿. It gives information about the decolonization process, and explores its consequences. Chapter 3, ¿The Impacts of HIV/AIDS and Malaria on the Labor Force¿. It analyzes the impact of those diseases in the labor force. Chapter 4 ¿The Green Revolution and the Agriculture Sector¿, explores the concepts of Green Revolution, its success in India and its history in Mozambique. Chapter 5, finally, centers on conclusions, findings and recommendations.